Nucleated RBCs in umbilical cord blood as marker in cases of fetal asphyxia - Shrivastava, Ayush; Vagha, Jayant; Borkar, Rajendra (International Journal of Contemporary Pediatrics, 2017)
Background: World health organization (WHO) has defined perinatal asphyxia as a failure to initiate and sustain breathing at birth. HIE is one of the most common complication in an asphyxiated neonate because of its serious long term neuromotor sequalae among the survivors. Nucleated red blood cells (NRBC) count in umbilical cord of newborns is been suggested as a sign of birth asphyxia. As the present markers are not accurate in diagnosis and assessing the severity of fetal asphyxia, this study was undertaken to find the values of NRBCs in normal and asphyxiated neonates and the correlation of NRBCs with birth asphyxia. Methods: Eighty neonates with asphyxia along with eight healthy newborns were undertaken for two years study period. Maternal and neonatal information was recorded follow by clinical and laboratory evaluation. NRBC levels was determined per 100 white blood cells (WBC). After discharge, immediate follow-up of asphyxiated infants was performed. Neonates were divided into two groups, with favorable and unfavorable outcome based on discharge or death. Results: We observed that NRBC count with more than 10 per 100 WBC/mm3, had sensitivity of 88.75% and specificity of 100% in predicting complications of asphyxia, while in NRBC count with more than 10, the sensitivity and specificity were 88.75% and of 100%, respectively. Conclusions: We demonstrate that NRBC/100 WBC can be used as prognostic marker for neonatal asphyxia, which in combination with the severity of asphyxia could indicate high infant mortality, immediate outcome and complications of asphyxia